Results of structural analysis of medical appointments of quercetin drugs and its derivatives in Ukraine - Bobokalo, Serhii; Almakaieva, Lyudmila; Panfilova, Hanna; Tsurikova, Oksana (ScienceRise: Pharmaceutical Science, 2019)
The aim: to analyze the structure of medical prescriptions for quercetin and its derivatives in Ukraine Materials and methods. We used data from an expert survey of doctors from 25 cities of Ukraine, which was conducted during 2017-2018. The survey involved doctors of various specialties who had «very high» (k ≥ 0.91), «high» (k = 0.71-0.90) and «satisfactory» (k = 0.51-0.70) level of competence. This indicator was determined using five coefficients (k1+n), which characterized the level of theoretical and applied training of specialists in the organization of the medical and diagnostic process for patients suffering from various types of angiopathies. We used the historical, analytical, comparative, systemic, logical, hypothetical-deductive, mathematical and statistical methods, as well as the expert survey method. Results. It was found that the largest number of appointments (51.82%) was made by therapists/family doctors, and the smallest - by endocrinologists (3.6%). The vast majority of respondents (except for allergologists and endocrinologists) prescribed these drugs in treatment according to the main diagnosis of the patient. At the same time, only therapists/family doctors and cardiologists prescribed quercetin and its derivatives in a wide range of development of the clinical picture of the pathology, namely the main diagnosis, with its complications and associated diseases. Doctors of all specialties, except for otolaryngologists noted the use of quercetin and its derivatives in the treatment of concomitant pathologies of sick patients. The first position in the structure of medical appointments (1st level of ICD-10) was taken by appointments in the treatment of I-diseases of the circulatory system (78.97%), the second – by J-diseases of the respiratory system (11.30%), and the third – K-digestive system diseases (6.04%). In the structure of prescriptions for patients with cardiovascular pathologies, the largest share was made in the treatment of angina pectoris (49.60%), in the second position – chronic ischemic heart disease (21.61%), and in the third – other cerebrovascular diseases (10.60%). Conclusions. It was proved that the highest prescribing rates of quercetin and its derivatives were carried out by therapists/family doctors in the treatment of diseases of the cardiovascular system according to the main diagnosis, its complications and associated pathologies. The low level or lack of prescription of drugs of this group in doctors of other specialties requires further research in the indicated direction